Children’s Literature of Kazakhstan in the Context of World Literature as the Basis of National Identity - Eleonora, Seisenbiyeva; Dauren, Mukhamadiev; Zhanakul, Sametova; Zhanar, Aitova; Kuralay, Tulebayeva; Nurgul, Ismagulova (Journal of Ecohumanism, 2024)
Children’s literature plays a vital role in shaping the identity of young readers by conveying cultural values, historical narratives, and national heritage. In Kazakhstan, children’s literature has evolved as a significant cultural asset, serving as a medium for promoting national identity and social cohesion in a rapidly modernizing world. This research explores the role of children’s literature in Kazakhstan, emphasizing its impact on the development of national identity, and positioning it within the broader context of world literature. The paper investigates the works of prominent Kazakh children’s authors, analyzing how their narratives represent and reflect Kazakh cultural traditions, values, and history, while also engaging with global literary trends and themes. Through a comparative lens, the study examines the influence of Soviet-era literature, post-independence transformations, and the globalization of children’s literature on the shaping of Kazakh national consciousness. By utilizing a qualitative methodology, this paper draws on literary analysis, historical context, and interviews with educators and literary scholars to understand how Kazakh children’s literature has contributed to the formation of national identity. The study also considers the extent to which global literary trends have shaped or influenced local literary traditions. Results indicate that while global influences are undeniable, Kazakh children’s literature remains rooted in its unique cultural, linguistic, and historical context. Furthermore, this research highlights the ongoing challenges faced by Kazakh children’s literature in balancing national heritage with the pressures of globalization. This paper concludes by discussing the need for the continued development of children’s literature in Kazakhstan as a means of preserving and promoting national identity in a globalized world.